Physioxia enhances T‐cell development ex vivo from human hematopoietic stem and progenitor cells. (15th August 2020) - Shin, Dong‐Yeop; Huang, Xinxin; Gil, Chang‐Hyun; Aljoufi, Arafat; Ropa, James; Broxmeyer, Hal E.
Abstract: Understanding physiologic T‐cell development from hematopoietic stem (HSCs) and progenitor cells (HPCs) is essential for development of improved hematopoietic cell transplantation (HCT) and emerging T‐cell therapies. Factors in the thymic niche, including Notch 1 receptor ligand, guide HSCs and HPCs through T‐cell development in vitro. We report that physiologically relevant oxygen concentration (5% O2, physioxia), an important environmental thymic factor, promotes differentiation of cord blood CD34+ cells into progenitor T (proT) cells in serum‐free and feeder‐free culture system. This effect is enhanced by a potent reducing and antioxidant agent, ascorbic acid. Human CD34+ cell‐derived proT cells in suspension cultures maturate into CD3+ T cells in an artificial thymic organoid (ATO) culture system more efficiently when maintained under physioxia, compared to ambient air. Low oxygen tension acts as a positive regulator of HSC commitment and HPC differentiation toward proT cells in the feeder‐free culture system and for further maturation into T cells in the ATO. Culturing HSCs/HPCs in physioxia is an enhanced method of effective progenitor T and mature T‐cell production ex vivo and may be of future use for HCT and T‐cell immunotherapies. Abstract : Thymic microenvironment in vivo is at low oxygen tension. Physioxia mimics the thymic atmospheric niche and enhances human cord blood HSC commitment and progenitor cell differentiation to progenitor/precursor T cells and maturation to T cells. Vitamin C mimics physioxia and intensifies effects of physioxia on T‐cell development in serum‐ and feeder‐free cultures and artificial thymic organoids.